2007
DOI: 10.1016/j.physletb.2007.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Unifying inflation with ΛCDM epoch in modified f(R) gravity consistent with Solar System tests

Abstract: We suggest two realistic f (R) and one F (G) modified gravities which are consistent with local tests and cosmological bounds. The typical property of such theories is the presence of the effective cosmological constant epochs in such a way that early-time inflation and late-time cosmic acceleration are naturally unified within single model. It is shown that classical instability does not appear here and Newton law is respected. Some discussion of possible anti-gravity regime appearence and related modificatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
173
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 511 publications
(181 citation statements)
references
References 24 publications
6
173
1
1
Order By: Relevance
“…This is because the ISW effect anti-correlates with the LSS for n < O(1000), and the sign of the cross-correlation function determines the lower bound (15). Note that the galaxy bias in Ref.…”
Section: Comparison With Observationsmentioning
confidence: 94%
See 2 more Smart Citations
“…This is because the ISW effect anti-correlates with the LSS for n < O(1000), and the sign of the cross-correlation function determines the lower bound (15). Note that the galaxy bias in Ref.…”
Section: Comparison With Observationsmentioning
confidence: 94%
“…Therefore, this is not problematic, and we also confirmed that using the galaxy bias of the ΛCDM model does not significantly change the results of chi-squared analysis. The lower bound (15) changes within only 10 percent even when we assume the bias as free parameters. This is because the constraint on the model parameter n is determined by the sign of the cross-correlation function, which is almost independent of nature of bias.…”
Section: Comparison With Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, if the conformal equivalence between f (R) theories and scalar-tensor theories is used, it is necessary that the effective mass acquired by the new scalar degree of freedom is unnaturally large [30]. Some f (R) theories that pass cosmological and solar system tests have been proposed [31][32][33]. However, it is also subject of debate if the conformal equivalence can be used in order to extract physical predictions from this models, especially predictions which involve perturbations [34].…”
Section: Comparison With the Treatment Of Perturbations In Other Modementioning
confidence: 99%
“…Since the Schwarzschild metric is consistent with observations of the solar system, spherically symmetric solutions of a viable theory of f(R) gravity for the vacuum should have a satisfactory limit of Schwarzschild metric. As yet, the discussion on the weak field limit of this f (R) = R + µ 4 /R theory of gravity is done and there are a few papers which claim different results [13][14][15][16][17][18][19][20]. In the recent works, authors have discussed f (R) = R ± µ 4 /R theory of gravity for the case of weak field limit and obtained perturbation terms in the metric potential components which are independent from the localized mass as source of inhomogeneous curvature and initial value conditions [21,22].…”
Section: Introductionmentioning
confidence: 99%